Comparing the Effects of Cognitive-Behavioral Group Therapy and Mindfulness-Based Cognitive Therapy on Multidimensional Pain Symptoms in Breast Cancer Patients - Nasrin Goodarzi; Javid Peymani; Hasan Ashayeri; Farahnaz Meschi; Mehrdad Sabet; Mohammad-Esmaeil Akbari (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2021)
Background and Aim: In every age of history, human beings have been afflicted with the fear of disease. Undoubtedly, cancer is among the most concerning diseases; cancer pain is among the major pains. The present study aimed to compare the effects of cognitive-behavioral group therapy and mindfulness-based cognitive therapy on multidimensional pain symptoms in patients with breast cancer. Methods & Materials: The present study was applied concerning the purpose and applied a quasi-experimental with pretest-posttest, a two-month follow-up, and control group design. The statistical population was all women with breast cancer referring to Tehran Cancer Research Center in 2018 who were selected by convenience sampling method, consisting of 30 patients. They were randomly divided into two groups of intervention and the control group. The repeated-measures Analysis of Variance (ANOVA) was used to analyze the obtained data. The research instrument was a multidimensional pain questionnaire (West Hyun-Yale) to evaluate multiple pain indices. Results: The current study results suggested that cognitive-behavioral therapy and mindfulness-based cognitive therapy were effective on pain experience (P<0.001); however, there was no significant difference between the intervention groups respecting pain experience. Conclusion Based on the present research findings, cognitive-behavioral therapy and mindfulness-based cognitive therapy impacted the management and pain intensity of patients with breast cancer.